Development of Concrete Incorporating Recycled Aggregates, Hydrated Lime and Natural Volcanic Pozzolan - Natividad Garcia-Troncoso (MDPI AG, 2021)
Recycling of construction and demolition waste is a central point of discussion throughout the world. The application of recycled concrete as partial replacement of mineral aggregates in concrete mixes is one of the alternatives in the reduction of pollution and savings in carbon emissions. The combined influence of the recycled crushed concrete, lime, and natural pozzolana on the mechanical and sustainable properties of concrete materials is firstly proposed in this study. In this research, unconventional construction materials are employed to produce concrete: the recycled crushed concrete is used as coarse aggregate, while lime and natural pozzolana are used as a partial replacement for cement. Substitutions of 10%, 20%, 50% of gravel are made with recycled aggregates, and 2%, 5%, 10% of cement with lime and natural pozzolan. Tests on the fresh and hardened properties, destructive (compressive strength) and non-destructive tests (sclerometer rebound and ultrasound) of mixtures are carried out. It is shown that the use of recycled materials can provide an increase in compressive strength of up to 34% with respect to conventional concrete. Life cycle cost and sustainability assessments indicate that concrete materials incorporating recycled aggregate possess good economic and environmental impacts.